PERBANDINGAN KECERDASAN LINGUISTIK ANAK USIA 5-6 TAHUN DI TK YANG MEMFOKUSKAN PROGRAM TAHFIDZ DAN TK YANG TIDAK MEMFOKUSKAN PROGRAM TAHFIDZ - Annisa Selitri Yean; Zulkifli Zulkifli; Nurlita Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract:The aim of this research is to find out whether there is a significant difference in the linguistic intelligence of children aged 5-6 years in kindergartens that focus on the tahfidz program and kindergartens that do not focus on the tahfidz program. The type of research taken is comparative research. The steps taken in this comparative research are: Potential and problems, gathering information, and limited field testing. Data collection techniques in this study are by means of observation, interviews, and documentation. The instrument used consisted of two types of validation, namely instrument validation regarding children's linguistic intelligence and assessment instruments. Meanwhile, for a limited field test, using an observation sheet. The data analysis technique used for this research is statistical analysis method. Based on calculations from several tests conducted, it indicates that there is a comparison of the linguistic development of children whose kindergarten focuses on the tahfidz program with kindergartens that do not focus on the tahfidz program. It can be concluded that there is a significant comparison in the linguistic development of children whose kindergarten focuses on the tahfidz program with kindergartens that do not focus on the tahfidz program.Key Words: Tahfidz, Linguistic Intelligence of Children Age 5-6 Years.